Methodology for choosing a route for transport of dangerous goods - case study - Starčević, Slobodan M.; Gošić, Aleksandar M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
In the Serbian Armed Forces, oil and petroleum products are transported primarily for military units and institutions. The route for the movement of vehicles is selected during the transportation planning process. This paper describes a methodology for the selection of a route for the transport of dangerous goods and its application on one particular case in the Serbian Armed Forces. Introduction The existence of high risk or the possibility of hazards that can occur when transporting dangerous goods requires the maximum responsibility of all participants in the transportation process. The Serbian Armed Forces in their regular activities implement a number of tasks of transport of dangerous goods within the territory of the Republic of Serbia. Despite the fact that the Serbian Armed Forces, during the course of their duties, are exempted from the application of the provisions of the law governing the transport of dangerous goods in the Republic of Serbia, it is necessary to consider the risks that arise during the implementation of the transport of dangerous goods. The methodology for the selection of a route for the transport of dangerous goods The transport of dangerous goods is a type of transport linked with major risks and potentially most serious harm to humans and the environment. For this purpose, it is necessary to take certain measures to reduce the level of risk by implementing a set of procedures and gathering information on the characteristics of dangerous goods, the number of incidents in the past, the extent of the impact on the population and the environment as well as on the capacity of the relevant services in case of incidents. The determination of the hazards of dangerous goods being transported is a very important step because if the types and degrees of risk of dangerous goods as well as the zone of influence of cargo are not defined properly, it is not possible to estimate the level of risk. After identifying the type of hazardous cargo that is transported, it is necessary to determine the total amount to be transported to the required area for whicha route for the transport of dangerous goods is selected. In its third step, the methodology defines the movement of dangerous goods between each fixed source of dangerous goods and its target destination on the basis of which, in the fourth step, the routes are loaded with an ideal flow of traffic of dangerous goods and subsequently the dangerous load-carrying capacity of the route is determined. In the fifth step, which represents the final step in the hazard identification and the analysis of consequences, the limitations (physical limitations , ecological zones , limitations regarding legal regulations, etc.) that may affect the choice of a route are defined. ( The selection of a route for the transport of oil and petroleum products for the needs of the Army of Serbia The methodology for the selection of routes for the movement of vehicles carrying dangerous goods can be applied in the selection of routes for the transport of oil and petroleum products from the warehouse of the Serbian Army in Knić to the garrison of Belgrade. Characteristics of oil and petroleum products as hazardous cargo Oil and petroleum products (gasoline , diesel , etc.) belong to class 3 of dangerous goods - flammable liquids. The characteristics that define each type of dangerous goods, in addition to its physical and chemical properties, are also the characteristics of the hazard, ie. the type and degree of risk. Another characteristic of risk for each hazardous cargo is the degree of hazard. The degree of hazard is defined by the so-called "Packaging groups". The last feature of the selected types of dangerous goods which is of great significance is the size of the zone of influence. It can be concluded that, after an incident has occured, certain types of hazardous cargo can cause a variety of effects. A very important feature of dangerous goods, in addition to its type and degree of hazard, is the zone of its influence, i.e. the radius from the source to the limit of the negative impact of hazardous cargo caused by leakage from the cargo, i.e. transport vessel. Characteristics of the transport of oil and petroleum products for Army units in the Belgrade garrison For a detailed insight into the characteristics of the transport of oil and petroleum products for the needs of the Serbian Army garrison in Belgrade, it is necessary to identify the locations where dangerous goods are stored, produced, etc, or, in other words, to identify fixed sources of dangerous goods. When total amounts are determined, depending on their types, it is necessary to establish all modes of transportation of dangerous goods from these sources to target destinations. The first step in defining the transport demands of the Army in the city of Belgrade is the determination of the total amount of oil and petroleum products transported for the needs of army units deployed in the garrison of Belgrade. After defining the distribution of transport demands in time, it is also necessary to define the characteristics of transport demands in the area., The characteristics of the source -target destination movement are first to be defined. Accordingly, the methodology for the selection of routes for the movement of vehicles carrying dangerous goods will be applied for choosing a route and analysing the risk for the selected route for the movement of military tank trucks that transport oil and petroleum products from the storage in Knić to the "Topčider" barracks in Belgrade. Risk assessment by sections within the selected route The two main components that define the risk in the risk analysis are: likelihood of incidents and extent of their impact or a negative impact on the elements exposed to the risk of incidents. Certain parameters affect the probability of occurrence of incidents, while the second group of parameters defines the extent of the consequences of the occurrence of the incident. In order to test a potential route for the transport of oil and petroleum products, and each section separately, it is necessary to determine the value of each of the parameters affecting the level of risk. In order to achieve this, it is necessary to have a large database of each parameter separately and calculate their values ​​within the zone of influence of dangerous goods for each section separately. Comparing the degree of risk of that section with the degree of the allowed risk is carried out by using a risk matrixwhere the comparison with the acceptable levels of risk is performed based on the probabilities and values ​​of the risk level of potential consequences. Conclusion One of the procedures in planning the transport of hazardous cargo (such as the transport of oil and petroleum products for the units of the Army garrison in Belgrade) for the Army, , is to assess the route in terms of risk occurrence of the incident prior to choosingit for the realization of the transport task.